2007
DOI: 10.1111/j.1532-5415.2007.01310.x
|View full text |Cite
|
Sign up to set email alerts
|

An Outreach Program Improved Osteoporosis Management After a Fracture

Abstract: This longitudinal retrospective cohort study evaluated implementation of an intervention to improve management of osteoporosis after a fracture in a nonprofit group-model health maintenance organization (HMO) in the U.S. Pacific Northwest with 480,000 members and electronic medical record data. Participants were female HMO members aged 67 and older who sustained a qualifying clinical fracture(s) and who had not received a bone mineral density (BMD) measurement or osteoporosis treatment in the 12 months before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…Second, prior studies have identified patient adherence to osteoporosis medications as a barrier to treatment, 33,34 and the onceā€yearly inā€hospital administration of IV bisphosphonates may effectively circumvent this barrier. Third, intervention studies to improve osteoporosis treatment after hip fracture through enhanced outpatient followā€up have resulted in only modest improvements, 10,17,19,35,36 suggesting that additional interventions, including inā€hospital initiation, may be needed to improve rates of appropriate treatment dramatically 21 . Fourth, the American Orthopedic Association has led the development of the ā€œOwn the Boneā€ initiative, which aims to improve the ā€œtreatment of osteoporosis after fragility fractureā€ and focuses on hospitalization, recognizing that the ā€œseriousness of the fracture episode provides physicians with a definite ā€˜teachable momentā€™ in which it is possible to make a major impact on patients' and primary care physicians' behaviors.ā€ 20,37 Last, the National Osteoporosis Foundation's ā€œNational Action Plan for Bone Healthā€ focuses on fracture as a sentinel event, stating that, ā€œJust as a heart attack is seen as a sentinel event for treating cardiovascular disease, a first fragility fracture must be seen as an intervention opportunity.ā€ 38 Compared with rates of inā€hospital lipid diagnosis in cardiovascular patients (81% in 2006), 38 the low rates of inā€hospital osteoporosis treatment for hip fracture patients in this study serve as a call to action, as well as a baseline measure for current and future improvement initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…Second, prior studies have identified patient adherence to osteoporosis medications as a barrier to treatment, 33,34 and the onceā€yearly inā€hospital administration of IV bisphosphonates may effectively circumvent this barrier. Third, intervention studies to improve osteoporosis treatment after hip fracture through enhanced outpatient followā€up have resulted in only modest improvements, 10,17,19,35,36 suggesting that additional interventions, including inā€hospital initiation, may be needed to improve rates of appropriate treatment dramatically 21 . Fourth, the American Orthopedic Association has led the development of the ā€œOwn the Boneā€ initiative, which aims to improve the ā€œtreatment of osteoporosis after fragility fractureā€ and focuses on hospitalization, recognizing that the ā€œseriousness of the fracture episode provides physicians with a definite ā€˜teachable momentā€™ in which it is possible to make a major impact on patients' and primary care physicians' behaviors.ā€ 20,37 Last, the National Osteoporosis Foundation's ā€œNational Action Plan for Bone Healthā€ focuses on fracture as a sentinel event, stating that, ā€œJust as a heart attack is seen as a sentinel event for treating cardiovascular disease, a first fragility fracture must be seen as an intervention opportunity.ā€ 38 Compared with rates of inā€hospital lipid diagnosis in cardiovascular patients (81% in 2006), 38 the low rates of inā€hospital osteoporosis treatment for hip fracture patients in this study serve as a call to action, as well as a baseline measure for current and future improvement initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…(21) Others have evaluated factors associated with FSF but could not separate those with atypia, due to lack of radiographic review. Abrahamsen and colleagues (17) described higher rates of oral glucocorticosteroid use and similar rates of bisphosphonate dispensings in FSFs compared to hip fractures.…”
Section: Discussionmentioning
confidence: 99%
“…At the provider level, fi nancial incentives historically have not motivated changes in practice patterns [39,40]. Continuing medical education that provides recommended guidelines and physician performance audit and feedback has only a modest effect on practice change [41,42ā€¢,43].…”
Section: Provider-targeted Interventionsmentioning
confidence: 99%